Greenwashing: Dirt is not good - MATHEW, DR. SUSAN; R R, DR. VINOD (The journal of contemporary issues in business and government, 2021)
Several studies have reported the willingness of consumers to pay a premium for green products. By adopting green practices, the firm not only opens a market for environment lovers, but also arouse a sort of public sentiment among existing consumers, and also generate positive cash flow. However, given the circumstances, we cannot accept all environmental claims made by firms at face value. There have been instances where firms have been using the concept of ‘green’ with an intention to mislead the customer. They seem to have been emphasizing on the green label as a method to build a false brand image. This is known as ‘green washing’. Going by the literature, there is no dearth for studies which have examined the antecedent of green purchase behavior. However, to the best of our knowledge, studies on green washing practices followed by firms and its impact on the economy seem to be highly ignored. Accordingly, this study focuses on examining the impact of green washing on the economy. Further we also evaluate the reason why firms tend to go behind green washing and suggest ways to curb this tendency.